2018
DOI: 10.30848/pjb2019-2(5)
|View full text |Cite
|
Sign up to set email alerts
|

Changes based on oxidative stress in metolachlor and atrazine treated maize seedlings

Abstract: The present study investigated biochemical effects of Atrazine (0, 200μM , 500 μM and 1000 μM) and Metolachlor (0, 100μM , 500 μM and 1000 μM) concentrations applied to 15-day-old seedlings of three maize varieties (Zea mays L., cv. Saccharata, cv. Danona, and cv. Advanta 2898) for 48 hr. Hydroponic environment was preferred for all treatments for the seedlings. Compared to their controls, GSH/GSSG ratio was decreased, SOD activity was increased, and CAT activity was also decreased/decreased in root/leaf of At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Although the primary site of action of this herbicide is still uncertain and strictly dependent on plant species, the active compound can interfere with plant growth and development, triggering oxidative stress, inhibiting long chain fatty acids , and cell division, and compromising the membrane permeability of root cells . In graminaceous crops, such as rice or maize, metolachlor caused oxidative stress and decreased plant biomass production. Our results showed that Megafol significantly reduced the toxic effects of this chemical (Figures and ). No literature reports document such an ability of a biostimulant to counteract the phytotoxic effect of a herbicide.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although the primary site of action of this herbicide is still uncertain and strictly dependent on plant species, the active compound can interfere with plant growth and development, triggering oxidative stress, inhibiting long chain fatty acids , and cell division, and compromising the membrane permeability of root cells . In graminaceous crops, such as rice or maize, metolachlor caused oxidative stress and decreased plant biomass production. Our results showed that Megafol significantly reduced the toxic effects of this chemical (Figures and ). No literature reports document such an ability of a biostimulant to counteract the phytotoxic effect of a herbicide.…”
Section: Discussionmentioning
confidence: 62%
“…Plants subjected to abiotic stresses can undergo the oxidation of unsaturated fatty acids, which is provoked by reactive oxygen species (ROS) . Herbicides are well-known to give rise to oxidative perturbations that can increase or decrease enzymatic activities such as catalases , and peroxidases depending on the species . For this reason, the content of MDA, a product of lipid peroxidation, was investigated in plants treated with metolachlor in combination or not with Megafol, since this parameter is an important indicator of lipid degradation in response to the treatments.…”
Section: Discussionmentioning
confidence: 99%